Factors influencing the selection criteria of Saudi board orthopedic surgery applicants: a national survey of program directors - Suhail S. AlAssiri; Alwaleed A. Alshahir; Sami I. Al Eissa; Fahad H. Al Helal; Faisal M Konbaz; Majed S. Abaalkhail; Rayed M. Al Jehani; Abdullah F. Mohabbat; Khalid A. AlSheikh (BMC Medical Education, 2024)
Abstract Background Annually, medical students vie to secure a seat with an orthopedic residency program. This rigorous competition places orthopedic surgery as one of the most competitive specialties in the medical field. Although several international studies have been published regarding the factors that influence program directors when choosing their ideal applicant, the data for Saudi Arabia in that regard is absent. Methods In this cross-sectional study, we aimed to survey all orthopedic program directors regarding the factors that influence them when choosing their ideal orthopedic surgery applicant. A survey was sent to all program directors via email during the month of August 2022. A reminder was sent 2 weeks later to maximize the response rate. The survey was completed by 22 out of 36 orthopedic program directors, which gave us a response rate of 61.11%. Results In this study, 22 orthopedic surgery program directors responded to our survey. When program directors were asked to rank the factors of residency selection criteria, the top ranked factors were good impression on interviews; prior experience in orthopedic surgery with, for example, electives; and performance on ethical questions during interviews, with means of 9.18, 8.95, and 8.82 out of 10, respectively. Furthermore, program directors preferred letters of recommendation from recommenders that they personally know, clinical experience such as electives taken at the program director’s institution, and the quality of publications as the most important aspects of research. Most program directors (90.9%) relied on their residents’ and fellows’ opinions when selecting candidates, and 77.3% did not think gender has an influence on selection of applicants. Conclusion By providing comprehensive data regarding the factors that influence and attract program directors of orthopedic surgery when choosing residency candidates. With the data provided by this study, applicants for orthopedic surgery have the advantage of early planning to build a strong application that may help persuade program directors to choose them.